Quality of Life of Hypertensive Patients Undergoing Chronic Disease Management Program during the COVID-19 Pandemic - Lolo, Widya Astuty; Citraningtyas, Gayatri; Mpila, Deby Afriani; Wijaya, Heri; Poddar, Sandeep (Kesmas, 2022)
The COVID-19 pandemic has restricted some common activities for hypertensive patients undergoing the Chronic Disease Management Program/Program Pengelolaan Penyakit Kronis in primary health care, decreasing the quality of life. This study aimed to measure the quality of life of hypertensive patients undergoing the Chronic Disease Management Program at primary health care of Manado City, North Sulawesi Province, Indonesia, during the COVID-19 pandemic and determine the factors influencing hypertension such as sex, age, education, employment status, monthly income and duration of hypertension. This cross-sectional study was carried out on 150 hypertensive patients randomly sampled at primary health care from June to September 2021. The data were analyzed using the Mann-Whitney test. The quality of life of non-complicated hypertensive patients was higher than those with complications. The utility value and the visual analog scale of hypertensive patients with and without complications were 0.808±0.13 and 80.2±8.16 and 0.761±0.17 and 75.1±7.56, respectively. The quality of life of hypertensive patients without complication is better than that of hypertensive patients with complication.